Evaluasi efektivitas tingkat kepatuhan wajib pajak dalam memenuhi kewajiban perpajakannya - Anisinta Paso; wulan Dri Puspita (University of Merdeka Malang, 2020)
This study aims to evaluate the effectiveness of the compliance level of taxpayers (WP) in fulfilling their tax obligations. The object of this research is KPP Pratama Malang Utara as an agency that secures state revenue from the tax sector. Data collection techniques in this study were carried out using literature, interviews, and observation methods, while data analysis in this study was carried out by collecting data, analyzing it, then explaining the findings related to the problems encountered to draw conclusions and suggestions. The results showed that the level of taxpayer compliance in fulfilling their tax obligations related to tax payments and SPT reporting at KPP Pratama Malang Utara, both showed an unstable situation. The effectiveness calculation is not able to prove that the level of effectiveness of tax revenue and annual tax return reporting is increasing. This is caused by non-compliance and ignorance of taxpayers in fulfilling their tax obligations.